Phylogeography of Rhinichthys cataractae (Teleostei: Cyprinidae): pre‐glacial colonization across the Continental Divide and Pleistocene diversification within the Rio Grande drainage. (10th January 2014) - Kim, Daemin; Conway, Kevin W.
<x xml:space="preserve">Abstract</x> The longnose dace, Rhinichthys cataractae, is a primary freshwater fish inhabiting riffle habitats in small headwater rivers and streams across the North American continent, including drainages east and west of the Continental Divide. The mitochondrially encoded cytochrome b gene (1140 bp) and 2298–2346 bp of the nuclear‐encoded genes S7 and RAG1 were obtained from 87 individuals of R. cataractae (collected from 17 sites throughout its range) and from several close relatives. Phylogenetic analyses recovered a monophyletic R. cataractae species‐group that contained Rhinichthys evermanni, Rhinichthys sp. 'Millicoma dace', and a non‐exclusive R. cataractae. Within the R. cataractae species‐group, two well‐supported lineages were identified, including a western lineage (containing R. evermanni, R. sp. 'Millicoma dace' and individuals of R. cataractae from Pacific slope drainages) and an eastern lineage (containing individuals of R. cataractae from Arctic, Atlantic, and Gulf slope drainages). Within the eastern lineage of R. cataractae, two well‐supported groups were recovered: a south‐eastern group, containing individuals from the Atlantic slope, southern tributaries to the Mississippi River, and the Rio Grande drainage; and a north‐eastern group, containing individuals from the Arctic slope and northern tributaries to the Mississippi River. Estimates of the timing of divergence within the R. cataractae species‐group, combined with ancestral area‐reconstruction methods, indicate a separation between the eastern and western lineages during the Pliocene to early‐Pleistocene, with a direction of colonization from the west of the Continental Divide eastward. Within the southern portion of its range, R. cataractae likely entered the Rio Grande drainage during the Pleistocene via stream capture events between the Arkansas River (Mississippi River drainage) and headwaters of the Rio Grande. A close relationship between populations of R. cataractae in the Rio Grande drainage and the adjacent Canadian River (Mississippi River drainage) is consistent with hypothesized stream capture events between the Pecos (Rio Grande drainage) and Canadian rivers during the late‐Pleistocene. The population of R. cataractae in the lower Rio Grande may have become separated from other populations in the Rio Grande drainage (upper Rio Grande and Pecos River) and Canadian River during the late‐Pleistocene, well before initiation of recent and significant anthropogenic disturbance within the Rio Grande drainage. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 317–333.